IMPROVEMENT OF LEGAL AND ORGANIZATIONAL MECHANISMS FOR PREVENTING CRIMES COMMITTED IN CYBERSPACE (International journal of artificial intelligence, 2026)
This article examines the improvement of legal and organizational mechanisms for preventing crimes committed in cyberspace in the context of the rapid development of digital technologies. The growing scale of cybercrime poses serious threats to national security, public order, and the protection of individual rights and freedoms. The purpose of the study is to analyze existing legal frameworks and institutional practices aimed at combating cybercrime and to identify effective mechanisms for its prevention.The research employs methods such as legal analysis, comparative study, and systematic review of regulatory documents and law enforcement practices. The findings indicate that effective prevention of cybercrime requires not only the strengthening of criminal liability but also the development of organizational coordination, interagency cooperation, and preventive monitoring systems. Special attention is given to the role of digital forensics, cyber monitoring units, and public awareness initiatives in reducing cyber threats.The study concludes that improving legal norms, enhancing organizational capacity of law enforcement agencies, and promoting preventive measures based on modern technologies are essential for ensuring cybersecurity and protecting society from cyber-related crimes. The results of this research may be used in developing policy recommendations and improving practical measures for cybercrime prevention.